The Influence of Organizational Culture and Empowerment on Commitment to the Organization through Employee Work Motivation - Hadiwinata, Nandar; Sunaryo, Widodo; Yusnita, Nancy (Journal of Social Studies Arts and Humanities (JSSAH), 2023)
This study aims to increase employee organizational commitment at PT Batara Indah through efforts to develop organizational culture variables, empowerment, and work motivation. The population in this study amounted to 155 employees of the production division with a sample of 112 people using the Slovin formula with an error tolerance of 5%. Collecting data using a questionnaire using a simple random sampling technique. The results of this study resulted in the following conclusions: 1. There is a direct and significant positive influence of organizational culture on work motivation. The strength of the influence of organizational culture and work motivation is 0.929 () and organizational culture contributes to work motivation of 86.2% with the regression equation ; 2. Organizational culture has a positive and significant direct effect on organizational commitment. The strength of the influence of organizational culture and commitment to the organization is 0.981 () and organizational culture contributes to organizational commitment by 96.2% with the regression equation ; 3. There is a direct positive and significant effect of work motivation on commitment to the organization. The strength of the influence of work motivation and commitment to the organization is 0.950 () and work motivation contributes to organizational commitment by 90.2% with the regression equation ; 4. There is a direct positive and significant effect of employee empowerment on organizational commitment. The magnitude of the influence of employee empowerment and commitment to the organization is 0.945 () and employee empowerment contributes to commitment to the organization by 89.3% with the regression equation ; 5. There is a direct positive and significant effect of employee empowerment on work motivation. The magnitude of the influence of employee empowerment and work motivation is 0.964 () and employee empowerment contributes to work motivation of 92.9% with the regression equation ; 6. There is a positive and significant indirect effect of organizational culture on organizational commitment through work motivation. The magnitude of the influence of organizational culture on organizational commitment through work motivation is 0.929 () with the regression equation ; 7. There is a positive and significant indirect effect of employee empowerment on organizational commitment through work motivation. The magnitude of the influence of employee empowerment on organizational commitment through work motivation is 0.964 () with the regression equation .